Minat Beli Memediasi Pengaruh E-Service Quality Dan Promosi Terhadap Keputusan Pembelian Di Shopee (Studi Kasus Pada Mahasiswa Manajemen Ukrida 2017) - Melitina Tecoalu; Kelvin Yonathan; Hery Winoto Tj (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
Technological developments support an increase in online buying and selling activities in marketplaces that have turned conventional transactions into digital ones. The quality of services and promotions offered have also turned digital. The purpose of this study was to examine the effect of e-service quality and promotion on purchasing decisions at Shopee which are mediated by purchase intention. By using a sample of 60 students of the 2017 UKRIDA Management Departement with a purposive sampling technique. The data analysis technique used in this research is Structural Equation Modeling (SEM) using the SmartPLS version 3.0 software. The results obtained in this study indicate that there is an effect of e-service quality on purchasing decisions and purchase intentions, while promotion has no effect on purchasing decisions. Meanwhile, mediation of purchase intention strengthens the influence of e-service quality and promotion on purchasing decisions. Keywords: e-service quality, promotion, purchasing decisions, purchase intention